Study of the Opportunities and Impacts of Naturalization for Expatriates to Obtain Indonesian Citizen Status (Case Study of Expatriates in Lingga District) - Nurpadila Zulenzky; Hambali Hambali; Indra Primahardani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This research is motivated by several problems faced by foreigners in applying for Indonesian citizenship. The purpose of this study is to find out how big the opportunity for expatriates to get Indonesian Citizenship status is and to find out what impacts are felt by the expatriates themselves and the surrounding community. The benefit of the results of this research is to be a source of learning for all groups. This research method is qualitative, the data collection instruments used are interviews and documentation. The informants in this study are the authorities and expatriates. Opportunity conclusions are drawn using cross-probability tables, while the impact is taken from interview conclusions. The conclusion from the implementation of Law No. 12 of 2006, namely points 2.6 and 8, is still not optimally fulfilled by the applicant (expatriate). For example point 8, to fulfill these requirements the applicant uses the services of other people such as 'brokers' or the like. As for points 1,3,4,5 and 7, the opportunity for a large applicant is that they can meet these requirements. For example, point 1 is when they apply for their age of 18 years or are married. As for the positive and negative impacts, both for themselves (expatriates) and the community, respondents agreed to feel a positive impact.